Comparative effect of the extended use of acids for surface treatment of osseointegrated implants. A laboratory study - Mendes, G. N.; Takeshita, W. M. [UNESP]; Brasileiro, B. F.; Trento, C. L. (My University, 2024)
Aim The aim of this study is to comparatively analyze the effects of extended acid usage, up to the fifth time, on the treatment of dental implant surfaces on their apex, middle, and neck regions. Materials and Methods Implant samples (n=10) were analyzed using a scanning electron microscope, and their captures by implant region (apex, body, and neck) were processed using ImageJ software. The generated Ra and Rq data of the samples were assessed using the Kruskal-Wallis test and the Dunn post-hoc test. Results The treatment groups showed no statistical significance compared to the control group up to the fourth use. Therefore, extended acid usage is possible, but it is conditioned upon the number of acid reuses. However, in the 5th use, there was significant variation in the mean values of Ra and Rq in the Dunn post-hoc test. Conclusion Based on the obtained results, it can be concluded that using the same acid for dental implant surface treatment up to four times did not alter the dental implant surface roughness property. Nonetheless, further studies are necessary, particularly because there is limited data regarding this unexplored research topic in the implantology literature.
Keywords: Dental Implants; Metallurgy Industry; Surface properties; Treatment Surface